Konsep Ekonomi Buddhis : Strategi Pengumpulan dan Pengelolaan Kekayaan Berdasarkan Sutta Pitaka - Tri Saputra Medhācitto; Sukhitta Dewi; Sukodoyo Sukodoyo (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study aims to conduct an in-depth examination on the concept of Buddhist economic based on the principles of the Buddha’s teachings in the Sutta Pitaka. The methodology used in this research is descriptive qualitative with literature analysis, collecting data obtained from both primary and secondary sources. The primary source refers to the main Buddhist scripture, the Tipitaka, especially the Sutta Pitaka section. Secondary sources include books, journals, and articles relevant to the topic, which help to enrich the discussion on the concept of Buddhist economic. The research results show that the Buddhist economic is an approach that integrates the principles of Buddha’s teachings with the practice of wealth accumulation and management based on ethics and morality. Buddhism is a religion that emphasizes moral practice, so the right way to accumulate wealth is by not neglecting Buddhist morality. Human welfare should not be achieved by harming other beings or damaging the environment. Proper wealth management is the wisdom in using wealth to support the achievement of welfare. This study provides an important contribution to Buddhist knowledge about the correct strategies for wealth accumulation and management that support economic growth and welfare while prioritizing morality.